Development of Contents for Effective Computer Programming Education in Curriculum of Elementary Schools - Kim, Jong-soo; Kwon, Soon-kak (Journal of Multimedia Information System, 2019)
In a variety of fields, highly developed technology is being combined to create a lot of value. In order to keep up with this global trend, the Ministry of Education, which is in charge of national education, continuously develops and applies content for creative education to textbooks. The continuous development of content for creative education is not only related to national interests, but also to the continued development of mankind. Today, the succession and development of human knowledge is in charge of the education system. Research into an effective educational system is necessary for effective succession of rapidly developing science and technology and building up technical personnel with such skills. In particular, the computer science field is faster in development than other scientific fields and has accumulated many technologies, indicating that it takes a lot of time and good teaching to foster talent that can effectively utilize the technology. In this paper, elementary school subjects were analyzed to achieve the purpose of cultivating talent in the field of computer science. In addition, we have investigated techniques related to computer programming learning not covered in elementary school subjects. So we developed content that students need to practice. Next, we taught the content to randomly selected elementary school students and assessed their educational effectiveness. As a result of training using the content we developed, 55.37% increased academic performance KCI Citation Count: 0